Impact of community based screening for hypertension on blood pressure after two years: regression discontinuity analysis in a national cohort of older adults in China - Chen, Simiao; Sudharsanan, Nikkil; Huang, Feng; Liu, Yuanli; Geldsetzer, Pascal; Bärnighausen, Till (The BMJ, 2019)
Objective To estimate the causal impact of community based blood pressure screening on subsequent blood pressure levels among older adults in China. - Design Regression discontinuity analysis using data from a national cohort study. - Setting 2011-12 and 2014 waves of the Chinese Longitudinal Healthy Longevity Survey, a national cohort of older adults in China. - Participants 3899 older adults who had previously undiagnosed hypertension. - Intervention Community based hypertension screening among older adults in 2011-12. - Main outcome measure Blood pressure two years after initial screening. - Results The intervention reduced systolic blood pressure: −6.3 mm Hg in the model without covariates (95% confidence interval −11.2 to −1.3) and −8.3 mm Hg (−13.6 to −3.1) in the model that adjusts additionally for demographic, social, and behavioural covariates. The impact on diastolic blood pressure was smaller and non-significant in all models. The results were similar when alternative functional forms were used to estimate the impact and the bandwidths around the intervention threshold were changed. The results did not vary by demographic and social subgroups. - Conclusions Community based hypertension screening and encouraging people with raised blood pressure to seek care and adopt blood pressure lowering behaviour changes could have important long term impact on systolic blood pressure at the population level. This approach could address the high burden of cardiovascular diseases in China and other countries with large unmet need for hypertension diagnosis and care.